(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2008)
Many Doctors do not follow proper documentation of medical Records. In fact many of them do not realize the importance of documenting their records thoroughly, thereby exposing them to frivolous charges of malpractice. This paper seeks to impress upon the importance of proper medical documentation and its medico legal significance. The materials are collected by reviewing medical records of KMC hospitals and Govt. Wenlock hospital, Mangalore, India along with medical registers of medical record departments of above-mentioned hospitals. For additional information the listed references were consulted.